2011
DOI: 10.1371/journal.pone.0019843
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Spectral Domain Optical Coherence Tomography (SD-OCT) in Multiple Sclerosis: The First Follow Up Study over Two Years

Abstract: Background“Non-invasive, faster and less expensive than MRI” and “the eye is a window to the brain” are recent slogans promoting optical coherence tomography (OCT) as a new surrogate marker in multiple sclerosis (MS). Indeed, OCT allows for the first time a non-invasive visualization of axons of the central nervous system (CNS). Reduction of retina nerve fibre layer (RNFL) thickness was suggested to correlate with disease activity and duration. However, several issues are unclear: Do a few million axons, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 33 publications
4
50
1
Order By: Relevance
“…Our results, however, are more in line with 2 other studies in which no significant decrease was observed in RNFL thickness during follow-up. 30,31 Discrepancies in RNFL change across studies may relate to differences in cohort characteristics. Our results raise the possibility that rates of RNFL thinning may be greater in cohorts with larger proportions of patients with prior ON.…”
Section: Results a Total Of 164 Ms/cis Patients (116 Rrms 24 Spms 1mentioning
confidence: 99%
“…Our results, however, are more in line with 2 other studies in which no significant decrease was observed in RNFL thickness during follow-up. 30,31 Discrepancies in RNFL change across studies may relate to differences in cohort characteristics. Our results raise the possibility that rates of RNFL thinning may be greater in cohorts with larger proportions of patients with prior ON.…”
Section: Results a Total Of 164 Ms/cis Patients (116 Rrms 24 Spms 1mentioning
confidence: 99%
“…Up till now, a reliable specific para-clinical marker neither for the diagnosis nor for monitoring disease activity of MS could yet be established (e.g. Aboul-Enein et al, 2010;Gilmore et al, 2010;Kuhle et al, 2007;Serbecic et al, 2010Serbecic et al, , 2011.…”
Section: Diagnostic Criteria and The Disease Course Of Msmentioning
confidence: 99%
“…11 Serbecic et al prospectively studied 37 RRMS and secondary progressive MS patients on two occasions with a median interval of 22.4 AE 0.5 months and did not find any significant changes between the baseline and follow-up RNFL patterns. 12 Another study reported no significant change in RNFL over 2 years in 46 MS patients without comparative data from healthy controls. 18 These studies support our results of almost stable RNFL thickness in MS patients during relatively short follow-up period.…”
Section: Discussionmentioning
confidence: 97%
“…reduced over time. 11,12 Henderson et al studied 34 patients with progressive MS on two occasions with a median interval of 575 days and 18 healthy controls with a median interval of 656 days. The MS patients had significant decreases in the baseline RNFL thickness and macular volume of their clinically unaffected eyes compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation